Our experience with pre-operative haemostatic assessment of paediatric patients undergoing adenotonsillectomy at Federal Medical Centre, Makurdi - Amali Adekwu; Agida Samuel Adoga; Terna Ambrose Gav (Wolters Kluwer Medknow Publications, 2016)
Background: In 2-4% of all patients requiring adenoidectomy, tonsillectomy or adenotonsillectomy, pre-operative screening tests for coagulation disorders are indicated to detect surgical bleeding complications. However, because of cost effect on the patients, the usefulness of these tests is being challenged. We therefore highlight our experience in paediatric patients undergoing adenoidectomy, tonsillectomy or both in our centre. Patients and Methods: This is a 3½-year analysis of the data of 165 paediatric patients who had adenoidectomy, tonsillectomy or both over the study period. The data collected included age, sex, procedure done and detailed clinical bleeding history. Results: A total of 165 children had either adenoidectomy or tonsillectomy, or both. There were 76 males and 89 females giving a male to female ratio of 1:1.2. Their ages ranged from 10 months to 18 years. Eighty-five (51.5%) patients had adenotonsillectomy, 48 (29.1%) and 32 (19.4%) had only tonsillectomies and adenoidectomies, respectively. Only 11 (6.7%) families volunteered the history of either prolonged bleeding with minor injury on the skin or occasional slight nose bleeding. Six (3.6%) patients including 3 of the children with positive family history had posttonsillectomy bleed, out of which 4 (66.7%) were moderate whereas the remaining 2 (33.3%) were severe bleeding, which was not statistically significant (P = 0.041). The two cases of severe bleeding had fresh whole blood transfused whereas the rest that had no bleeding issues were discharged home 48 h postoperatively. Conclusion: Our experience in this study suggests that detailed bleeding history is necessary as well as pre-operative haemostatic assessment, if available and affordable for paediatric patients undergoing adenotonsillectomy.